Characterising the anti-proliferative effects of metformin and assessing its efficacy in combination chemotherapy strategies in-vitro for the treatment of oesophageal squamous cell carcinoma - Jivan, Rupal (My University, 2015)
Oesophageal Squamous cell Carcinoma (OSCC) has a poor survival rate and is highly prevalent in southern Africa. Cisplatin is the standard therapeutic drug for OSCC, but has poor efficacy due to drug resistance and toxicity. Development of therapies that can be used to reduce the dose of cisplatin or offer a more effective tumour response is of great importance. Metformin is an anti-diabetic drug that has demonstrated anti-proliferative effects in various cancer types. Metformin’s potential as a chemotherapeutic drug is highlighted by its low toxicity profile, ability to reduce growth factor signalling, and toxic effects against cancer stem cells. In this study we combined metformin and cisplatin to find that whilst metformin reduced the proliferation of OSCC cell lines, it antagonised the effects of cisplatin. This was attributed to increased levels of reduced thiols as a consequence of enhanced glycolysis, which leads to the formation of reducing equivalents such as NADPH. Since metformin enhances the intracellular reducing potential, we combined metformin with drugs that are activated in reducing environments. Two copper bis(thiosemicarbazones), Cu-ATSM and Cu-GTSM, both retained their toxicity in the presence of metformin. Disulfiram (DSF), an established anti-alcoholism drug, has previously demonstrated chemotherapeutic potential when conjugated to copper (Cu-DSF). DSF and Cu-DSF both exerted potent cytotoxic effects against OSCC cell lines which were enhanced by metformin. Metformin increased intracellular copper accumulation when combined with DSF and we found that DSF perturbed proteasome function, as observed in other studies. Furthermore, we identified a novel target of DSF, the lysosome, and found that DSF reduces lysosomal pH, which led to increased accumulation of lysosomal protein aggregates, thereby inhibiting autophagy in OSCC cell lines. Therefore, the co-prescription of metformin and cisplatin is not advised for OSCC treatment. However metformin can be effectively combined with DSF, which inhibits multiple protein degradation pathways, to offer a novel treatment option for OSCC.
Keywords: Squamous cell carcinoma.; Esophagus--Cancer.; Cell differentiation.; Cancer.